Quasi-Static Investigations of 240-Bloom Gelatine for Ballistic Tests - Bartosz FIKUS; Norbert BASIŃSKI (Problemy Mechatroniki)
The paper presents the results of investigations of ballistic gel properties in quasi-static conditions. Specimens were prepared using the 240 Bloom gelatine, which was determined by product availability. Tests were carried out making use of a material testing machine to estimate the influence of gel share on stress-strain characteristics. Considered values of a gel mass content were equal to 10, 12, and 14%. Assumed parameters were determined on the material calibration stage conducted with steel balls with a diameter of 4.5 mm. The most significant influence of a gel content on mechanical properties of specimens were observed for a share of 10% and 12%. The conducted preliminary tests are a part of investigations aimed at assessment if it is possible to calibrate the ballistic gel making use of mechanical characteristics obtained in quasi-static tests without shooting.